A comparison of visual- and stereo-video based fish community assessment methods in tropical and temperate marine waters of Western Australia - holmes, T.; wilson, S.; Travers, M.; Langlois, T.; Evans, R.; Moore, G.; Douglas, R.; Shedrawi, G.; Harvey, Euan; Hickey, K. (American Society of Limnology and Oceanography, 2013)
Robust assessments of abundance and diversity are essential components of research programs aimed at detecting changes in marine fish assemblages through space and time. This study examined the comparability of Underwater Visual Census (UVC), and Diver Operated stereo-Video (Stereo-DOV) datasets collected across a wide latitudinal range (15°) on coral reefs and temperate rocky shores. There were some differences between methods with regards to both species richness and abundance, with UVC consistently recording higher measures of species richness. Differences were most pronounced at tropical locations where these measures were high. Differences in the characteristics of fish assemblages were primarily driven by UVC differentiating between scarid and pomacentrid species and detecting more cryptic species. When examined at higher taxonomic or functional levels however, there was greater comparability between the assemblages recorded byeach method, particularly in temperate locations. The UVC method also recorded higher abundances of species targeted by fishers in tropical/sub-tropical locations, and subsequently obtained a much higher proportion of length measurements for these species. Data collected using stereo-DOV took 2-3 times longer to obtain than with UVC due to extensive post-processing time required by the stereo-DOV method. This study shows that data collected by the two methods are most comparable in temperate locations, or when examined at higher taxonomic/functional levels. Comparisons should however be more cautious in higher diversity locations, or when assessing at finer taxonomic resolution. When assessing the suitability of either method, availability of time, funding, and relevant expertise should be primary considerations.